PENGUATAN SISTEM ADMINISTRASI AKADEMIK DAN NON AKADEMIK DI PRODI S1 AKUNTANSI - Ni Kadek Sinarwati (KRISNA: Kumpulan Riset Akuntansi, 2017)
Abstract The standard implementation of the learning process as part of the national standards of higher education, is an effort that can be done to improve the quality of learning and the academic atmosphere at colleges in order to achieve an increase in the value of accreditation Prodi as well as institutions. The general objective of this research is doing to support the action of priority program. increase the value of the accreditation institution through an increase in the value of the accreditation status of Undergraduate accounting, by way of improving the quality of the standard curriculum, learning and academic atmosphere, whereas the aim in particular is to make an effort for the strengthening of academic and nonacademic administration as well as knowing the factor in the Degree Program majoring in accounting. Academic administration strengthening efforts in research this is done through a standard evaluation of the learning process in primary competency courses. This research is a research institution of the Policy implemented by the method of comparative descriptive qualitative nature. The data type used is qualitative data comprising the device learning courses the main competencies, the standard implementation of the learning process and student perceptions against a standard implementation of the learning process. The data was collected by using the techniques of observation, interview and questionnaire. The data were analyzed using descriptive comparative analysis i.e. exposes the standard implementation of the real process of learning done at Prodi S1 Accounting then compare it to the standard process of learning which should be carried out in accordance with the standard process of book Edition 2015 Doc. No. 19 UJM Undiksha. The results showed that the implementation of standards of learning process in Undergraduate Accounting status of this being in the category is enough. Academic administration system strengthening efforts made through improvements in the learning process and filing up to the test of thesis, academic administration system strengthening efforts made through the arrangement of the book and the thesis contained in the Library departments. Keywords: system, administration, academic Penerapan standar proses pembelajaran sebagai bagian dari Standar Nasional Pendidikan Tinggi, merupakan upaya yang dapat dilakukan untuk meningkatkan kualitas pembelajaran dan suasana akademik di perguruan tinggi guna mencapai peningkatan nilai akreditasi prodi maupun institusi. Tujuan umum penelitian ini adalah melakukan aksi dukungan terhadap program prioritas Undiksha yakni meningkatkan nilai akreditasi institusi melalui peningkatan nilai akreditasi Prodi S1 Akuntansi, dengan cara meningkatkan kualitas standar kurikulum, pembelajaran dan suasana akademik., sedangkan tujuan khususnya adalah melakukan upaya penguatan administrasi akademik dan non akademik serta mengetahui faktor penghambatnya di Jurusan Akuntansi Program S1. Upaya penguatan administrasi akademik dalam penelitian ini dilakukan melalui evaluasi standar proses pembelajaran pada mata kuliah kompetensi utama. Penelitian ini merupakan penelitian Kebijakan Institusi yang dilaksanakan dengan metode deskriptif komparatif yang bersifat kualitatif. Jenis data yang digunakan adalah data kualitatif yang terdiri dari perangkat pembelajaran mata kuliah kompetensi utama, penerapan standar proses pembelajaran dan persepsi mahasiswa terhadap penerapan standar proses pembelajaran. Data dikumpulkan dengan menggunakan teknik wawancara, observasi dan kuesioner. Data dianalisis dengan menggunakan analisis deskriptif komparatif yakni memaparkan penerapan standar proses pembelajaran yang sesungguhnya terlaksana di Prodi S1 Akuntansi kemudian membandingkannya dengan standar proses pembelajaran yang seharusnya terlaksana sesuai dengan buku standar proses edisi 2015 Dok. No.19 UJM Undiksha. Hasil penelitian menunjukkan bahwa pelaksanaan standar proses pembelajaran di Prodi S1 Akuntansi berada dalam kategori cukup. Upaya penguatan sistem administrasi akademik dilakukan melalui pembenahan pada proses pembelajaran dan pengajuan sampai dengan ujian skripsi, upaya penguatan sistem administrasi akademik dilakukan melalui penataan buku dan skripsi yang terdapat di perpustakaan jurusan. Kata Kunci: Sistem, administrasi, akademik